Trends and Applications in Software Engineering Proceedings of the 6th International Conference on Software Process Improvement (CIMPS 2017) (Advances in Intelligent Systems and Computing, 2018)
This book includes a selection of papers from the 2017 International Conference on Software Process Improvement (CIMPS'17), presenting trends and applications in software engineering. Held from 18th to 20th October 2017 in Zacatecas, Mexico, the conference provided a global forum for researchers and practitioners to present and discuss the latest innovations, trends, results, experiences and concerns in various areas of software engineering, including but not limited to software processes, security in information and communication technology, and big data. The main topics covered are organizational models, standards and methodologies, software process improvement, knowledge management, software systems, applications and tools, information and communication technologies and processes in non-software domains (mining, automotive, aerospace, business, health care, manufacturing, etc.) with a demonstrated relationship to software engineering challenges.